A multifunctional composite anti-leakage tray and preparation method thereof

By using a composite structure of a base material layer, a regenerated buffer layer and a wear-resistant and corrosion-resistant layer in the anti-leakage tray, the problem of poor corrosion resistance of existing trays when using chemical reagents is solved, and the tray's high corrosion resistance and anti-corrosion properties are achieved. Leakage and impact resistance.

CN118685001BActive Publication Date: 2025-01-24CHANGZHOU BECOAN IND TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202410900578.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-05
Publication Date
2025-01-24
Estimated Expiration
2044-07-05

AI Technical Summary

Technical Problem

When using chemical reagents, it is difficult to effectively ensure its anti-seepage characteristics, especially the corrosion resistance of different solvents.

Method used

A composite anti-leakage tray composed of a base material layer, a regenerated buffer layer and a wear-resistant and corrosion-resistant layer is used. The wear-resistant and corrosion-resistant layer is composed of modified fillers, epoxy resin, amino-terminated silane coupling agents and additives. The surface forms a micro-nano secondary rough structure to improve corrosion resistance.

Benefits of technology

The pallet has achieved excellent corrosion resistance and anti-leakage performance, and can be used as an experimental console for a long time. It has high strength and impact resistance, can stably carry heavy objects, and provides safe anti-leakage guarantee.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004930357100000091
    Figure BDA0004930357100000091
  • Figure BDA0004930357100000092
    Figure BDA0004930357100000092
  • Figure BDA0004930357100000101
    Figure BDA0004930357100000101
Patent Text Reader

Abstract

The present application relates to the technical field of pallets, and specifically discloses a multifunctional composite anti-leakage pallet and a preparation method thereof, wherein the pallet includes a substrate layer, a regeneration buffer layer and a wear-resistant and corrosion-resistant layer from the inside to the outside; wherein the wear-resistant and corrosion-resistant layer is made of the following components in parts by weight: 25 to 45 parts of modified filler, 120 to 160 parts of epoxy resin, 82 to 110 parts of amino-terminated silane coupling agent, and 0.5 to 5 parts of auxiliary agent; the modified filler is a core-shell structure, and the shell layer of the modified filler is made of epoxy resin and amino-terminated silane coupling agent; the particle size of the modified filler is 100 to 800 nm. The anti-leakage pallet prepared in the present application can have excellent corrosion resistance, wear resistance, impact resistance and high load through the cooperation of the wear-resistant and corrosion-resistant layer, the regeneration buffer layer and the substrate layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of pallets, and more specifically, to a multifunctional composite anti-leakage pallet and a preparation method thereof. Background Art

[0002] As a transport vehicle, pallets can carry objects in large quantities and improve work efficiency. Pallets are generally made of polypropylene (PP) or high-density polyethylene (HDPE), which are lightweight, easy to clean, and high in strength. They are widely used in logistics, transportation, manufacturing and other industries.

[0003] At present, the pallets used in the chemical manufacturing industry are leak-proof pallets, and a leak-collecting tank is provided inside the leak-proof pallet. The leak-collecting tank can collect chemical reagents such as organic solvents, strong acids, strong alkalis, and salt solutions. The leak-proof pallet can not only carry chemical reagents, but also has multiple functions, such as being used as an experimental operation platform. When the leak-proof pallet is used as an experimental operation platform, it is difficult to guarantee its leak-proof properties only by relying on the corrosion resistance of the pallet material itself. The reason is that there is a large difference in the corrosion resistance of PP and HDPE to different solvents. For example, PP has good corrosion resistance to acids, but its corrosion resistance to organic solvents such as chloroform decreases. Therefore, how to further optimize the corrosion resistance of the leak-proof pallet is an urgent problem to be solved in this field. Summary of the invention

[0004] In response to the above-mentioned related issues, the present application provides a multifunctional composite anti-leakage tray.

[0005] In the first aspect, the present application provides a multifunctional composite anti-leakage tray, which adopts the following technical solution:

[0006] A multifunctional composite anti-leakage tray, comprising a base material layer, a regeneration buffer layer and a wear-resistant and corrosion-resistant layer from the inside to the outside;

[0007] Wherein, the wear-resistant and corrosion-resistant layer is made of the following components in parts by weight:

[0008] 25-45 parts of modified filler, 120-160 parts of epoxy resin, 82-110 parts of amino-terminated silane coupling agent, 0.5-5 parts of auxiliary agent;

[0009] The modified filler is a core-shell structure, and the shell layer of the modified filler is made of epoxy resin and amino-terminated silane coupling agent; the particle size of the modified filler is 100-800nm.

[0010] By adopting the above-mentioned technical scheme, the substrate layer in the present application is made of polypropylene, linear high-density polyethylene and other materials, and the substrate layer gives the anti-leakage pallet good mechanical strength to ensure that the anti-leakage pallet can carry heavy objects; the regenerated buffer layer is made of recycled rubber, and there is a pore structure inside the regenerated buffer layer, which can serve as a second anti-seepage barrier; at the same time, the regenerated buffer layer can disperse stress and reduce the possibility of the container of chemical reagents colliding with the inner wall of the pallet during transportation, causing the container to rupture; the wear-resistant and corrosion-resistant layer serves as the first anti-seepage barrier, and adopts the lotus leaf bionic principle, and a micro-nano secondary rough structure is formed on its surface. The wear-resistant and corrosion-resistant layer has a lower surface free energy, and there are a large number of air gaps on its surface, and these gaps form an air layer, which hinders the invasion of chemical reagent molecules, so that the wear-resistant and corrosion-resistant layer has good corrosion resistance.

[0011] The wear-resistant and corrosion-resistant layer uses epoxy resin and amino-terminated silane coupling agent as the main material to obtain modified polysiloxane containing flexible silane segments. The wear-resistant and corrosion-resistant layer has excellent toughness and good impact resistance. It is not easy to be damaged when the wear-resistant and corrosion-resistant layer is loaded with heavy objects. The modified filler has a core-shell structure. The shell layer of the modified filler is coated with modified polysiloxane, and the core uses spherical hard particles. The modified filler has good compatibility with the main material and can be fully dispersed in the main material. It is not easy to have clustered particles, ensuring the stable formation of the micro-nano secondary rough structure. At the same time, the shell layer can play a protective role, making the core particles not easily corroded and worn by chemical reagents, ensuring the integrity of the micro-nano secondary rough structure on the surface of the wear-resistant and corrosion-resistant layer.

[0012] The regenerated buffer layer is composed of waste rubber powder, epoxy resin, and amino curing agent. The epoxy resin contains polar ether bonds and hydroxyl groups. The bonding strength between the regenerated buffer layer and the wear-resistant and corrosion-resistant layer, as well as between the regenerated buffer layer and the substrate layer is high, and the layers are not easily separated. At the same time, epoxy resin, as an adhesive, can make the waste rubber powders fully bonded. The regenerated buffer layer uses waste rubber powder as the main raw material, which can greatly save production costs.

[0013] The material of the substrate layer includes but is not limited to polypropylene and linear high-density polyethylene. Polypropylene has high strength and heat resistance and is suitable for large loads and high-temperature environments, while linear high-density polyethylene has good toughness and impact resistance and is suitable for occasions subject to frequent impacts and vibrations. In this application, polypropylene is selected as the raw material for the substrate layer. Due to the provision of the regenerated buffer layer, the regenerated buffer layer can better reduce the impact of the outside world on the substrate layer. Therefore, the substrate layer made of polypropylene and the regenerated buffer layer cooperate to give the anti-leakage tray good impact resistance and strength.

[0014] It should be noted that the auxiliary agent in the present application includes a flame retardant, and the selection of flame retardants includes but is not limited to one or more of bromine flame retardants, phosphorus flame retardants, nitrogen flame retardants, silicone flame retardants and zinc stannate flame retardants; the use of a compound of organic flame retardants and inorganic flame retardants in the present application can greatly improve the flame retardant efficiency, and can obtain the UL-94V0 level with less addition.

[0015] To summarize, the present application forms a composite anti-leakage tray through a wear-resistant and corrosion-resistant layer, a regenerated buffer layer and a substrate layer, so that the anti-leakage tray has excellent corrosion resistance and anti-leakage performance, and can be used as a laboratory operating table for a long time; at the same time, the anti-leakage tray has high strength and good impact resistance, can stably carry heavy objects, and effectively play a long-term and anti-leakage safety guarantee role.

[0016] Furthermore, the modified filler is prepared according to the following steps:

[0017] An epoxy resin is diluted with an inactive diluent, spherical filler particles are added, stirred and dispersed to obtain a prefabricated liquid, the prefabricated liquid is dropwise added into an amino-terminated silane coupling agent, stirred and dispersed, filtered and dialyzed after the reaction is completed, and a modified filler is obtained; wherein the weight ratio of the epoxy resin, the amino-terminated silane coupling agent and the spherical filler particles is (5.26-5.84):(3.6-4.0):(3.0-3.5).

[0018] By adopting the above technical scheme, the weight ratio of epoxy resin, amino-terminated silane coupling agent and spherical filler particles is controlled so that the thickness of the shell layer is controlled within a moderate range. The modified filler can have both good wear resistance and good dispersion performance, which can ensure the long-term wear resistance and corrosion resistance of the wear-resistant and corrosion-resistant layer.

[0019] Furthermore, the particle size of the modified filler is controlled to be between 300 and 500 nm.

[0020] Furthermore, the content of the modified filler is 30 to 40 parts.

[0021] By adopting the above technical scheme, the content and particle size of the modified filler will affect the surface micro-nano secondary structure of the wear-resistant and corrosion-resistant layer. When the particle size is too large or the content is too high, large clusters are easily formed on the surface of the wear-resistant and corrosion-resistant layer, resulting in a decrease in surface roughness; when the particle size is small and the content is low, the surface roughness of the wear-resistant and corrosion-resistant layer is low, thereby reducing the corrosion resistance of the anti-leakage tray.

[0022] Furthermore, the epoxy resin is a polyphenol glycidyl ether epoxy resin.

[0023] Furthermore, the epoxy resin is any one or more of linear phenol formaldehyde epoxy resin, o-cresol formaldehyde epoxy resin, resorcinol formaldehyde epoxy resin, tetraphenol ethane tetraglycidyl ether, triphenol methane triglycidyl ether epoxy resin and pyrogallol epoxy resin.

[0024] Furthermore, the epoxy resin is resorcinol formaldehyde epoxy resin.

[0025] By adopting the above technical scheme, the polyphenol-type glycidyl ether epoxy resin has a rigid benzene ring structure and a high epoxy content, which can effectively improve the crosslinking density between the epoxy resin and the amino-terminated silane coupling agent, thereby increasing the crosslinking density of the wear-resistant and corrosion-resistant layer, enhancing the connection strength between the wear-resistant and corrosion-resistant layer and the regenerated buffer layer, and enhancing the heat resistance of the wear-resistant and corrosion-resistant layer, giving the anti-leakage pallet better wear resistance and corrosion resistance, and having less impact on the overall impact resistance of the anti-leakage pallet.

[0026] Furthermore, the epoxy value of the epoxy resin is 0.78 to 0.85 mol / 100g.

[0027] By adopting the above technical scheme, the epoxy equivalent of the epoxy resin is controlled. When the epoxy equivalent of the epoxy resin is controlled within a moderate range, the cross-linking density of the wear-resistant and corrosion-resistant layer can be maintained at a better level, the modified filler can be stably embedded in the wear-resistant and corrosion-resistant layer, the wear resistance of the anti-leakage tray is enhanced, and the possibility of increased brittleness caused by excessive strength of the wear-resistant and corrosion-resistant layer can be reduced.

[0028] Furthermore, the amino-terminated silane coupling agent is γ-aminoethylaminopropyltrimethoxysilane.

[0029] By adopting the above technical solution, γ-aminoethylaminopropyltrimethoxysilane contains two amino groups, which can enhance the cross-linking density of the wear-resistant and corrosion-resistant layer and the regeneration buffer layer, thereby ensuring the overall strength of the anti-leakage tray.

[0030] Furthermore, the regeneration buffer layer is made of the following raw materials:

[0031] 160-200 parts of waste rubber powder, 80-100 parts of epoxy resin, 54.8-68.6 parts of amino-terminated silane coupling agent, and 0.2-4 parts of auxiliary agent.

[0032] By adopting the above technical scheme, the regenerated buffer layer uses waste rubber powder as the main raw material, the epoxy resin is cured under the action of the amino-terminated silane coupling agent, and the waste rubber powder is dispersed in the epoxy resin-amino-terminated silane coupling agent system to form a regenerated buffer layer.

[0033] Furthermore, the substrate layer is made of polypropylene.

[0034] In a second aspect, the present application provides a method for preparing a multifunctional composite anti-leakage tray, which adopts the following technical solution:

[0035] A method for preparing a multifunctional composite anti-leakage tray comprises the following steps:

[0036] Forming of substrate layer;

[0037] Preparation of the regenerated buffer layer: the waste rubber powder is mixed with the epoxy resin, an amino-terminated silane coupling agent and an auxiliary agent are added, the mixture is stirred and poured on the substrate layer, and the mixture is cured to obtain the regenerated buffer layer;

[0038] Preparation of wear-resistant and corrosion-resistant layer: The modified filler is mixed with epoxy resin, an amino-terminated silane coupling agent and an auxiliary agent are added, the mixture is stirred and mixed, and then poured on the regenerated buffer layer, and cured to obtain the wear-resistant and corrosion-resistant layer.

[0039] By adopting the above technical solution, the preparation method of the anti-leakage tray of the present application is simple, and has good corrosion resistance, wear resistance and excellent mechanical properties. DETAILED DESCRIPTION

[0040] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the technical scheme of the present application is further described below in combination with preparation examples, embodiments and comparative examples.

[0041] Unless otherwise specified, the sources of the raw materials used in the following preparation examples, embodiments and comparative examples are as follows:

[0042] Resorcinol bisglycidyl ether type epoxy resin: brand 680#, epoxy value is 0.78~0.85mol / 100g;

[0043] Bisphenol A type epoxy resin: Brand: E-55, epoxy value is 0.55~0.56mol / 100g;

[0044] γ-Aminoethylaminopropyltrimethoxysilane: Brand: A-1120;

[0045] Spherical silica filler: particle size range: 50-100nm;

[0046] Polypropylene: Brand: EPS30R;

[0047] Waste rubber powder: customized product, average specific surface area is 3.76m 2 / g, particle size is 1~500μm;

[0048] Brominated flame retardant: Brand 8010, from Albemarle.

[0049] Preparation Example

[0050] Preparation Example 1

[0051] A modified filler is prepared according to the following steps:

[0052] 5.6 kg of epoxy resin 680# was diluted with ethyl acetate as an inactive diluent, and the volume ratio of ethyl acetate to epoxy resin 680# was 3:1; after dilution, 3.2 kg of spherical silica filler was added, and the mixture was stirred and dispersed at a speed of 1000 rpm, and stirred for 10 minutes to obtain a prefabricated liquid;

[0053] The preformed liquid was added dropwise to 4 kg of amino-terminated silane coupling agent A-1120. During the addition, the stirring speed in the reaction system was always maintained at 500 rpm until the addition was completed. The mixture was stirred at 20-25° C. for 6 h. After the reaction was completed, the mixture was filtered and finally dialyzed in ultrapure water to obtain the modified filler.

[0054] The modified filler is sieved to obtain a modified filler with a particle size of 300 to 500 nm.

[0055] Preparation Example 2-3

[0056] A modified filler, which is different from Preparation Example 1 in that the weight ratio of the epoxy resin, the amino-terminated silane coupling agent and the spherical silica filler is different;

[0057] Wherein, the weight ratio of epoxy resin, amino-terminated silane coupling agent and spherical silica filler in Preparation Example 2 is 5.26:3.6:3.5;

[0058] Wherein, the weight ratio of the epoxy resin, the amino-terminated silane coupling agent and the spherical silica filler in Preparation Example 3 is 5.84:4.0:3.0.

[0059] Preparation Example 4-5

[0060] A modified filler, which differs from Preparation Example 1 in that the speed of stirring and dispersing is different:

[0061] In the preparation example 4, the spherical silica filler was stirred and dispersed at a speed of 500 rpm; the stirring speed was always maintained at 100 rpm in the reaction system; and after sieving, a modified filler with a particle size of 500 to 800 nm was obtained;

[0062] In the preparation example 5, the spherical silica filler was stirred and dispersed at a speed of 2000 rpm; the stirring speed was always maintained at 1000 rpm in the reaction system; and the modified filler with a particle size of 100 to 300 nm was obtained after sieving.

[0063] Example

[0064] Example 1

[0065] A multifunctional composite anti-leakage tray is produced according to the following steps:

[0066] Preparation of the substrate layer: polypropylene EPS30R and masterbatch are mixed in proportion, put into a mold, and a rotational molding process is used to fuse the raw materials through high-temperature sintering, and then the substrate layer is obtained after cooling;

[0067] Preparation of regenerated buffer layer: 1.8 kg of waste rubber powder was taken and put into 9 kg of epoxy resin 680#, and stirred and dispersed at a speed of 1000 rpm. Then 6.16 kg of γ-aminoethylaminopropyltrimethoxysilane and 0.1 kg of brominated flame retardant 8010 were added to the system, and stirred and dispersed at a speed of 500 rpm for 1 min. After stirring, the substrate layer was put into the mold, and the evenly mixed waste rubber powder-resin system was poured into the mold in batches, and the temperature was raised to 100°C for insulation reaction for 30 min to obtain a regenerated buffer layer;

[0068] Preparation of wear-resistant and corrosion-resistant layer: Take 4 kg of the modified filler prepared in Preparation Example 1, add it to 15 kg of epoxy resin 680#, stir and disperse it at a speed of 1000 rpm, then add 10.27 kg of γ-aminoethylaminopropyltrimethoxysilane and 1 kg of brominated flame retardant 8010 to the system, stir and disperse it at a speed of 500 rpm for 1 min, after stirring, put a regenerated buffer layer in the mold, pour the uniformly mixed modified filler-resin system into the mold in batches, heat it to 100 ° C and keep it warm for 1 hour to obtain a wear-resistant and corrosion-resistant layer;

[0069] The thickness ratio of the substrate layer, the regeneration buffer layer and the wear-resistant and corrosion-resistant layer is 3:1:1.

[0070] Embodiment 2-4

[0071] A multifunctional composite anti-leakage tray is different from Example 1 in that the modified filler, epoxy resin 680# and γ-aminoethylaminopropyltrimethoxysilane are added in different amounts in the wear-resistant and corrosion-resistant layer, as follows:

[0072] In Example 2, the amount of modified filler added is 2.5 kg, the amount of epoxy resin 680# added is 12 kg, and the amount of γ-aminoethylaminopropyltrimethoxysilane added is 8.2 kg;

[0073] In Example 3, the amount of modified filler added was 3.0 kg, the amount of epoxy resin 680# added was 13 kg, and the amount of γ-aminoethylaminopropyltrimethoxysilane added was 8.9 kg;

[0074] In Example 4, the added amount of the modified filler is 4.5 kg, the added amount of epoxy resin 680# is 16 kg, and the added amount of γ-aminoethylaminopropyltrimethoxysilane is 11 kg.

[0075] Embodiment 5-6

[0076] A multifunctional composite anti-leakage tray, which is different from Example 1 in that the particle size of the modified filler is different, as follows:

[0077] The modified filler in Example 5 is derived from Preparation Example 4;

[0078] The modified filler in Example 6 is derived from Preparation Example 5.

[0079] Embodiment 7-8

[0080] A multifunctional composite anti-leakage tray, which is different from Example 1 in that the shell thickness of the modified filler is different, as follows:

[0081] The modified filler in Example 7 is derived from Preparation Example 2;

[0082] The modified filler in Example 8 is derived from Preparation Example 3.

[0083] Example 9

[0084] A multifunctional composite anti-leakage tray, which differs from Example 1 in that the type of epoxy resin is different, as follows:

[0085] The epoxy resin 680# used in the shell layer, the wear-resistant and corrosion-resistant layer, and the regeneration buffer layer of the modified filler is replaced by bisphenol A epoxy resin E-55 in equal parts by weight.

[0086] Example 10

[0087] A multifunctional composite anti-leakage tray, which is different from Example 1 in that the type of amino-terminated silane coupling agent is different, as follows:

[0088] The weight proportions of γ-aminoethylaminopropyltrimethoxysilane A-1120 used in the shell layer, the wear-resistant and corrosion-resistant layer, and the regeneration buffer layer of the modified filler are replaced with KH-550.

[0089] Examples 11-12

[0090] A multifunctional composite anti-leakage tray is different from Example 1 in that the amounts of waste rubber powder, epoxy resin 680# and γ-aminoethylaminopropyltrimethoxysilane added in the regenerated buffer layer are different, as follows:

[0091] In Example 11, the amount of waste rubber powder added was 1.6 kg, the amount of epoxy resin 680# added was 8 kg, and the amount of γ-aminoethylaminopropyltrimethoxysilane added was 5.48 kg;

[0092] In Example 12, the added amount of the modified filler is 2.0 kg, the added amount of epoxy resin 680# is 10 kg, and the added amount of γ-aminoethylaminopropyltrimethoxysilane is 6.86 kg.

[0093] Comparative Example

[0094] Comparative Example 1

[0095] A tray, which is different from the first embodiment in that the tray is only composed of a substrate layer, and the thickness of the substrate layer is the same as the total thickness of the layers stacked in the first embodiment.

[0096] Comparative Example 2

[0097] A tray, which differs from the first embodiment in that the filler is different, as follows:

[0098] An equal amount of weight of spherical silica filler with a size of 300 to 500 nm is used to replace the modified filler.

[0099] Comparative Example 3

[0100] A tray, which differs from the first embodiment in that the filler is different, as follows:

[0101] An equal weight portion of a modified filler of 1 to 10 μm is used to replace a modified filler of 300 to 500 nm.

[0102] Performance Testing

[0103] Examples 1-12 and Comparative Examples 1-3 were made into test samples with external dimensions of 50×50×20 cm (internal leakage trough dimensions of 45×45×17.5 cm, thickness of 2.5 cm), and the following tests were performed:

[0104] 1. Corrosion resistance:

[0105] Since a drainage port is provided on the anti-leakage tray, when the drainage port is significantly deformed, it is difficult for the drainage port to be tightly sealed with the sealing plug, and the tray loses its anti-seepage effect; therefore, the test sample is immersed in a test pool, and 36wt% hydrochloric acid (number A), 30wt% sodium hydroxide solution (number B), chloroform (number C) and saturated ammonium chloride solution (number D) are placed in the test pool in different partitions, and the immersion temperature is controlled to change cyclically at -10 to 40°C, and the drainage port is taken as the observation object, and the time when the drainage port is significantly deformed is recorded. The longer the time when the significant deformation occurs, the better the corrosion resistance;

[0106] 2. Wear-resistant properties:

[0107] The surface of the test sample was polished with 600-mesh sandpaper, the polishing load was 1 kg, and the polishing times were 10 times; after friction, the test sample was immersed in a test pool, and 36wt% hydrochloric acid (number A), 30wt% sodium hydroxide solution (number B), chloroform (number C) and saturated ammonium chloride solution (number D) were placed in the test pool, and the immersion temperature was controlled to change cyclically at -10 to 40°C, and the drain port was taken as the observation object, and the time when obvious deformation appeared at the drain port was recorded. The longer the obvious deformation time appeared, the better the wear resistance;

[0108] 3. Load test:

[0109] Place objects in the spill groove of the pallet, continue to increase the weight, and record the maximum weight that causes the pallet to deform;

[0110] 4. Impact test:

[0111] The test sample is lifted to a height of 10m, a 10kg object is placed in the leak trough, and then released to allow it to fall freely onto a hard surface, and the degree of damage after the impact is evaluated; if cracks appear on the test sample, it is a defective product; if no cracks appear on the surface, it is a qualified product.

[0112] Test results

[0113] Table 1. Test results of Example 1 and Comparative Examples 1-3

[0114]

[0115] Table 2. Test results of Examples 1-6

[0116]

[0117]

[0118] Table 3. Test results of Examples 1, 7-12

[0119]

[0120] Combining the data of Example 1 and Comparative Example 1 and Table 1, it can be seen that: in terms of structure, Comparative Example 1 is only provided with a substrate layer, and the thickness of Comparative Example 1 and Example 1 is the same. Although the load-bearing weight of Comparative Example 1 is 1.44 times that of Example 1, the production cost is also significantly increased. After cost accounting, the production cost of Comparative Example 1 is 1.8 times that of Example 1; and, Comparative Example 1 shows good corrosion resistance to sulfuric acid, but the corrosion resistance to organic solvents such as chloroform is limited, and the immersion time for leakage does not exceed 6 months, while Example 1 shows good corrosion resistance to strong acids, strong alkalis, organic solvents and salt solutions. At the same time, Example 1 shows excellent impact resistance in the impact test, and no damage such as cracks occurs under load. However, a small amount of cracks appeared in Comparative Example 1, indicating that the regenerated buffer layer has a certain buffering effect.

[0121] Combining the data of Example 1 and Comparative Example 2 and Table 1, it can be seen that: in Comparative Example 2, the surface of the silica filler lacks the shell material, and the problem of partial agglomeration occurs in the wear-resistant and corrosion-resistant layer. The micro-nano secondary rough structure on the surface of the wear-resistant and corrosion-resistant layer is destroyed, resulting in the deterioration of the hydrophobic and oleophobic properties of the wear-resistant and corrosion-resistant layer. Chemical reagents can infiltrate the surface of the wear-resistant and corrosion-resistant layer, and the wear-resistant and corrosion-resistant layer is prone to failure in a short time.

[0122] Combining the data of Example 1 and Comparative Example 3 and Table 1, it can be seen that the modified filler in Comparative Example 3 is too large, reaching the micron level, and the micro-nano secondary roughness structure cannot be formed on the surface of the wear-resistant and corrosion-resistant layer, resulting in a decrease in the surface roughness and a decrease in the corrosion resistance of the contact between the chemical reagent and the wear-resistant and corrosion-resistant layer.

[0123] Combining the data of Examples 1-6 and Table 2, it can be seen that: Example 1 and Examples 2-4 form a single comparison, and the only difference is that the content of the modified filler has changed; Example 1 and Examples 4-5 form a single comparison, and the only difference is that the particle size of the modified filler has changed; the changes in the particle size and content of the modified filler affect the surface microstructure of the wear-resistant and corrosion-resistant layer. When the particle size is too large or the content is too much, the modified filler is easy to stack, large clusters appear, and the surface roughness of the wear-resistant and corrosion-resistant layer is reduced; when the particle size is too small or the content is less, the surface roughness of the wear-resistant and corrosion-resistant layer is small; therefore, how to control the dispersion of the modified filler in the resin system has a significant effect on the corrosion resistance of the pallet.

[0124] Combining the data of Example 1, Examples 7-12 and Table 3, it can be seen that the selection of epoxy resin and the selection of amino-terminated silane coupling agent have a great influence on the cross-linking density of the resin system of the wear-resistant and corrosion-resistant layer. The wear resistance of bisphenol A epoxy resin and KH-550 is significantly reduced, and they are prone to deformation in a short time when immersed in organic solvents and salt solutions, resulting in leakage.

[0125] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0126] Moreover, the above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the attached claims.

Claims

1. A multifunctional composite anti-leakage tray, characterized in that: It includes, from inside to outside, a base material layer, a regeneration buffer layer, and a wear-resistant and corrosion-resistant layer; Wherein, the wear-resistant and corrosion-resistant layer is made of the following components in parts by weight: 25-45 parts of modified filler, 120-160 parts of epoxy resin, 82-110 parts of amino-terminated silane coupling agent, 0.5-5 parts of auxiliary agent; The modified filler is a core-shell structure, and the shell layer of the modified filler is made of epoxy resin and amino-terminated silane coupling agent; the particle size of the modified filler is 300-500nm; The modified filler is prepared according to the following steps: An epoxy resin is diluted with an inactive diluent, spherical filler particles are added, stirred and dispersed to obtain a prefabricated liquid, the prefabricated liquid is dropwise added into an amino-terminated silane coupling agent, stirred and dispersed, filtered and dialyzed after the reaction is completed, and a modified filler is obtained; wherein the weight ratio of the epoxy resin, the amino-terminated silane coupling agent and the spherical filler particles is (5.26-5.84):(3.6-4.0):(3.0-3.5).

2. A multifunctional composite anti-leakage tray as claimed in claim 1, characterized in that: The content of the modified filler is 30 to 40 parts.

3. The multifunctional composite anti-leakage tray according to claim 1, characterized in that: The epoxy resin is a polyphenol type glycidyl ether epoxy resin.

4. A multifunctional composite anti-leakage tray as claimed in claim 3, characterized in that: The epoxy value of the epoxy resin is 0.78 to 0.85 mol / 100g.

5. The multifunctional composite anti-leakage tray according to claim 1, characterized in that: The amino-terminated silane coupling agent is γ-aminoethylaminopropyltrimethoxysilane.

6. The multifunctional composite anti-leakage tray according to claim 1, characterized in that: The regeneration buffer layer is made of the following raw materials: 160-200 parts of waste rubber powder, 80-100 parts of epoxy resin, 54.8-68.6 parts of amino-terminated silane coupling agent, and 0.2-4 parts of auxiliary agent.

7. The multifunctional composite anti-leakage tray according to claim 1, characterized in that: The substrate layer is made of polypropylene.

8. A method for preparing a multifunctional composite anti-leakage tray according to any one of claims 1 to 7, characterized in that: The steps include: Forming of substrate layer; Preparation of the regenerated buffer layer: the waste rubber powder is mixed with the epoxy resin, an amino-terminated silane coupling agent and an auxiliary agent are added, the mixture is stirred and poured on the substrate layer, and the mixture is cured to obtain the regenerated buffer layer; Preparation of wear-resistant and corrosion-resistant layer: The modified filler is mixed with epoxy resin, an amino-terminated silane coupling agent and an auxiliary agent are added, the mixture is stirred and mixed, and then poured on the regenerated buffer layer, and cured to obtain the wear-resistant and corrosion-resistant layer.

Citation Information

Patent Citations

  • Nucleated polypropylene composition

    CN106471052A

  • Polypropylene composite material with high impact resistance and high bearing capacity and preparation method and application thereof

    CN111171450A

  • Wear-resistant corrosion-resistant super-hydrophobic composite coating and preparation method thereof

    CN113698850A

  • Novel wood tray

    CN215246229U

  • Heat-sealing particle coated with epoxy resin and its production

    JP1998054990A